Corona bewegt - auch die Bildungswissenschaft Bildungswissenschaftliche Reflexionen aus Anlass einer Pandemie - Krause, Sabine; Breinbauer, Ines Maria; Proyer, Michelle (Verlag Julius Klinkhardt, 2021)
The present volume takes its starting point in the crisis situation surrounding Covid-19. It aims to counteract the uncertainty and the break with what was previously seen as "normality" by means of academic practices. Involved in educational research and teaching, which in the face of the pandemic are re-locating and re-shaping themselves in a variety of ways, the authors turn to fundamental determinations of educational relations in their ideational, categorial, social and material re-locations. In doing so, they also focus on topics that have so far been rather marginal in educational studies, but which are emerging as future research topics, for example, the mechanisation of interaction.